(3GdeLehY GdePgH ef bhGYO GdePgHs - (3UdGM GdOjf Ndjd Hf cjcdOi GdYdGFis; (3UdGM GdOjf GdYdGFj , UdGM GdOjf CHh SYjO,J (B761 (3g` s
(3ChdgG (B:s
(3jHJOF HbGYOI Yfg Udi Gddg Ydjg hSde Cfg bGd (B( (3EPG CeQJce HCeQ aCJhG efg eG ESJWYJe (B) s
(3BNQgG (B:s
(3hEf ahJ eG jSJOQc cGdEbQGQ HGdYjf hGdTgGOI s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B126s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs